Fourteen-day vonoprazan and low- or high-dose amoxicillin dual therapy for eradicating Helicobacter pylori infection: A prospective, open-labeled, randomized non-inferiority clinical study - Hu, Yi; Xu, Xin; Liu, Xiao-Shun; He, Cong; Ouyang, Yao-Bin; Li, Nian-Shuang; Xie, Chuan; Peng, Chao; Zhu, Zhen-Hua; Xie, Yong; Shu, Xu; Zhu, Yin; et al. (Frontiers in Immunology, 2023)
We previously reported that vonoprazan-amoxicillin (VA) dual therapy for 7 or 10 days failed to achieve satisfied efficacy for Helicobacter pylori (H. pylori) eradication. We aimed to explore the efficacy of VA dual therapy for 14 days as first-line treatment for H. pylori infection. This was a single center, prospective, open-labeled, randomized non-inferiority clinical study conducted in China. Treatment naïve H. pylori infected patients were randomized to receive VPZ 20 mg b.i.d. in combination with low dose (1000 mg b.i.d.) or high dose (1000 mg t.i.d) amoxicillin for 14 days. 13C-urea breath tests were used to access the cure rate at least 4 weeks after treatment. 154 patients were assessed and 110 subjects were randomized. The eradication rate of VPZ with b.i.d. amoxicillin or t.i.d. amoxicillin for 14 days was 89.1% and 87.3% by intention-to-treat analysis, respectively, 94.1% and 95.9% by per-protocol analysis, respectively. The eradication rate and incidence of adverse events were not different among the two groups. VPZ with b.i.d. or t.i.d. amoxicillin for 14 days provides satisfactory efficacy as a first-line treatment for H. pylori infection in China.